Perencanaan Pemerintah Dalam Peningkatan Produksi Dan Harga Kelapa Sawit Petani Di Desa Mumpa Pasca Pandemi Covid 19 - Syahfitri, Triyana; Audina, Mila; Ferynaldo, Raymond; Nurbaiti, Nurbaiti; Wati, Ina (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2023)
The development of oil palm plantations has an important meaning to increase regional and national economic growth in terms of; creating added value, investment growth, output contributing to foreign exchange and even oil palm plantation activities have had positive or beneficial external influences on the surrounding area. The problem faced in this research is how the government plans to increase the production and price of farmer's palm oil in Mumpa Village after the Covid-19 pandemic and what are the inhibiting factors and supporting factors for government planning to increase the production and price of farmer's palm oil in Mumpa village after the Covid pandemic -19. The method used in this study is a qualitative method in which researchers conduct observations, interviews and discussions directly in Mumpa Village while carrying out Thematic KKN. From the results of the discussion, palm oil is a national strategic commodity because it has a long utilization chain so that there are many benefits that can be taken, including replacing the role of petroleum which is a non-renewable resource as fuel and produces various derivative products. which can be utilized which resulted in an increase in the processing industry for palm oil derivative products. The large number of these industries will result in a lot of employment and generate an increase in foreign exchange for the country so that the economy in Indonesia increases.